Pengaruh Karakteristik CEO, Kualitas Audit, dan Corporate Governance terhadap Penyajian Kembali Laporan Keuangan - Muhammad Arif Yafi; Poppy Nurmayanti; Ulfa Afifah (Universitas Prasetiya Mulya, 2025)
This study aims to examine the influence of CEO characteristics, audit quality and corporate governance on the restatement of financial statements. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange website from 2019-2023. The research sample was selected using the Purposive Sampling technique and 30 companies that met the criteria were obtained, with a total sample of 150 observations. The data analysis method used is logistic regression analysis. The results of the study show that CEO education and audit quality have a significant effect on the restatement of financial statements. Meanwhile, CEO tenure, CEO age, size of the board of commissioners, independent board of commissioners and size of the audit committee have no effect on the restatement of financial statements.